Ozone Responsive Gene Expression as a Model for Describing Repeat Exposure Response Trajectories and Interindividual Toxicodynamic Variability In Vitro. (30th October 2021) - Bowers, Emma C; Martin, Elizabeth M; Jarabek, Annie M; Morgan, David S; Smith, Hannah J; Dailey, Lisa A; Aungst, Emily R; Diaz-Sanchez, David; McCullough, Shaun D
Abstract: Inhaled chemical/material exposures are a ubiquitous part of daily life around the world. There is a need to evaluate potential adverse effects of both single and repeat exposures for thousands of chemicals and an exponentially larger number of exposure scenarios (eg, repeated exposures). Meeting this challenge will require the development and use of in vitro new approach methodologies (NAMs); however, 2 major challenges face the deployment of NAMs in risk assessment are (1) characterizing what apical outcome(s) acute assays inform regarding the trajectory to long-term events, especially under repeated exposure conditions, and (2) capturing interindividual variability as it informs considerations of potentially susceptible and/or vulnerable populations. To address these questions, we used a primary human bronchial epithelial cell air-liquid interface model exposed to ozone (O3 ), a model oxidant and ubiquitous environmental chemical. Here we report that O3 -induced proinflammatory gene induction is attenuated in repeated exposures thus demonstrating that single acute exposure outcomes do not reliably represent the trajectory of responses after repeated or chronic exposures. Further, we observed 10.1-, 10.3-, 14.2-, and 7-fold ranges of induction of interleukin (IL)-8, IL-6, heme oxygenase 1, and cyclooxygenase 2 transcripts, respectively, within in our population of 25 unique donors. Calculation of sample size estimates that indicated that 27, 24, 299, and 13 donors would be required to significantly power similar in vitro studies to identify a 2-fold change in IL-8, IL-6, HMOX1, and cyclooxygenase 2 transcript induction, respectively, to inform considerations of the uncertainty factors to reflect variability within the human population for in vitro studies.